Fungal Planet description sheets: 625-715 - Crous, P W; Wingfield, M J; Burgess, T I; Carnegie, A J; Hardy, G E St J; Smith, D; Summerell, B A; Cano-Lira, J F; Guarro, J; Houbraken, J; Lombard, L; Martín, M P; et al. (Persoonia, 2017)
Novel species of fungi described in this study include those from various countries as follows: Antarctica: Cadophora antarctica from soil. Australia: Alfaria dandenongensis on Cyperaceae, Amphosoma persooniae on Persoonia sp., Anungitea nullicana on Eucalyptus sp., Bagadiella eucalypti on Eucalyptus globulus, Castanediella eucalyptigena on Eucalyptus sp., Cercospora dianellicola on Dianella sp., Cladoriella kinglakensis on Eucalyptus regnans, Cladoriella xanthorrhoeae (incl. Cladoriellaceae fam. nov. and Cladoriellales ord. nov.) on Xanthorrhoea sp., Cochlearomyces eucalypti (incl. Cochlearomyces gen. nov. and Cochlearomycetaceae fam. nov.) on Eucalyptus obliqua, Codinaea lambertiae on Lambertia formosa, Diaporthe obtusifoliae on Acacia obtusifolia, Didymella acaciae on Acacia melanoxylon, Dothidea eucalypti on Eucalyptus dalrympleana, Fitzroyomyces cyperi (incl. Fitzroyomyces gen. nov.) on Cyperaceae, Murramarangomyces corymbiae (incl. Murramarangomyces gen. nov., Murramarangomycetaceae fam. nov. and Murramarangomycetales ord. nov.) on Corymbia maculata, Neoanungitea eucalypti (incl. Neoanungitea gen. nov.) on Eucalyptus obliqua, Neoconiothyrium persooniae (incl. Neoconiothyrium gen. nov.) on Persoonia laurina subsp. laurina, Neocrinula lambertiae (incl. Neocrinulaceae fam. nov.) on Lambertia sp., Ochroconis podocarpi on Podocarpus grayae, Paraphysalospora eucalypti (incl. Paraphysalospora gen. nov.) on Eucalyptus sieberi, Pararamichloridium livistonae (incl. Pararamichloridium gen. nov., Pararamichloridiaceae fam. nov. and Pararamichloridiales ord. nov.) on Livistona sp., Pestalotiopsis dianellae on Dianella sp., Phaeosphaeria gahniae on Gahnia aspera, Phlogicylindrium tereticornis on Eucalyptus tereticornis, Pleopassalora acaciae on Acacia obliquinervia, Pseudodactylaria xanthorrhoeae (incl. Pseudodactylaria gen. nov., Pseudodactylariaceae fam. nov. and Pseudodactylariales ord. nov.) on Xanthorrhoea sp., Pseudosporidesmium lambertiae (incl. Pseudosporidesmiaceae fam. nov.) on Lambertia formosa, Saccharata acaciae on Acacia sp., Saccharata epacridis on Epacris sp., Saccharata hakeigena on Hakea sericea, Seiridium persooniae on Persoonia sp., Semifissispora tooloomensis on Eucalyptus dunnii, Stagonospora lomandrae on Lomandra longifolia, Stagonospora victoriana on Poaceae, Subramaniomyces podocarpi on Podocarpus elatus, Sympoventuria melaleucae on Melaleuca sp., Sympoventuria regnans on Eucalyptus regnans, Trichomerium eucalypti on Eucalyptus tereticornis, Vermiculariopsiella eucalypticola on Eucalyptus dalrympleana, Verrucoconiothyrium acaciae on Acacia falciformis, Xenopassalora petrophiles (incl. Xenopassalora gen. nov.) on Petrophile sp., Zasmidium dasypogonis on Dasypogon sp., Zasmidium gahniicola on Gahnia sieberiana.Brazil: Achaetomium lippiae on Lippia gracilis, Cyathus isometricus on decaying wood, Geastrum caririense on soil, Lycoperdon demoulinii (incl. Lycoperdon subg. Arenicola) on soil, Megatomentella cristata (incl. Megatomentella gen. nov.) on unidentified plant, Mutinus verrucosus on soil, Paraopeba schefflerae (incl. Paraopeba gen. nov.) on Schefflera morototoni, Phyllosticta catimbauensis on Mandevilla catimbauensis, Pseudocercospora angularis on Prunus persica, Pseudophialophora sorghi on Sorghum bicolor, Spumula piptadeniae on Piptadenia paniculata.Bulgaria: Yarrowia parophonii from gut of Parophonus hirsutulus. Croatia: Pyrenopeziza velebitica on Lonicera borbasiana.Cyprus: Peziza halophila on coastal dunes. Czech Republic: Aspergillus contaminans from human fingernail. Ecuador: Cuphophyllus yacurensis on forest soil, Ganoderma podocarpense on fallen tree trunk. England: Pilidium anglicum (incl. Chaetomellales ord. nov.) on Eucalyptus sp. France: Planamyces parisiensis (incl. Planamyces gen. nov.) on wood inside a house. French Guiana: Lactifluus ceraceus on soil. Germany: Talaromyces musae on Musa sp. India: Hyalocladosporiella cannae on Canna indica, Nothophoma raii from soil. Italy: Setophaeosphaeria citri on Citrus reticulata, Yuccamyces citri on Citrus limon.Japan: Glutinomyces brunneus (incl. Glutinomyces gen. nov.) from roots of Quercus sp. Netherlands (all from soil): Collariella hilkhuijsenii, Fusarium petersiae, Gamsia kooimaniorum, Paracremonium binnewijzendii, Phaeoisaria annesophieae, Plectosphaerella niemeijerarum, Striaticonidium deklijnearum, Talaromyces annesophieae, Umbelopsis wiegerinckiae, Vandijckella johannae (incl. Vandijckella gen. nov. and Vandijckellaceae fam. nov.), Verhulstia trisororum (incl. Verhulstia gen. nov.). New Zealand: Lasiosphaeria similisorbina on decorticated wood. Papua New Guinea: Pseudosubramaniomyces gen. nov. (based on Pseudosubramaniomyces fusisaprophyticus comb. nov.). Slovakia: Hemileucoglossum pusillum on soil. South Africa: Tygervalleyomyces podocarpi (incl. Tygervalleyomyces gen. nov.) on Podocarpus falcatus.Spain: Coniella heterospora from herbivorous dung, Hymenochaete macrochloae on Macrochloa tenacissima, Ramaria cistophila on shrubland of Cistus ladanifer.Thailand: Polycephalomyces phaothaiensis on Coleoptera larvae, buried in soil. Uruguay: Penicillium uruguayense from soil. Vietnam: Entoloma nigrovelutinum on forest soil, Volvariella morozovae on wood of unknown tree. Morphological and culture characteristics along with DNA barcodes are provided.
Keywords: novel fungal species; systematics; LSU; ITS nrDNA barcodes